"É estudo do meio, não passeio!": a educação ambiental crítica através do vínculo entre escolas e unidades de conservação - Lobo, Lara Bittar (Universidade Federal de São Carlos, 2021)
This paper proposes to discuss the contribution of critical Environmental Education to the perspective of environmental studies carried out in Conservation Units, through the analysis of the Management Plan for the National Forest of Ipanema in concomitance with the laws and educational and environmental guidelines that dialogue about the presence of this educational perspective in formal and non-formal teaching spaces. This discussion took place through the rescue of the man-nature relationship through the concepts “nature”, “ecology” and “environment”, which enable the construction of critical Brazilian environmental thinking, together with the concept of “interdisciplinarity” and “study of the environment”, dialoguing with the dialectical approach to properly consider the histories of human intervention in the environment, where critical AE will converge directly on this dynamic. The discussion ends with the report of the experience of a public school teacher who, by exposing his whole process of articulation between the school and the conservation unit in question, demonstrates that his practice converges directly with the elements brought along job.
“It is a study of the environment, not a walk!”: Critical Environmental Education through the link between schools and conservation units
Keywords: Educação ambiental crítica; Ensino; Interdisciplinaridade; Estudo do meio; Unidades de Conservação; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA